Desingning An E-Voting Information System For Website-Based Village Head Elections : Perancangan Sistem Informasi E-Voting Pemilihan Kepala Desa Berbasis Website - Aditya Kurniawan; Yulian Findawati (Academia Open, 2021)
Voting in a democratic country is an important part of the means of choosing leaders. The village head election process in Indonesia still uses conventional voting methods, namely using ballot paper media in the election process. Voting that is carried out conventionally has several obstacles, including the lack of guaranteeing the authenticity of voters' votes, so that people think the results of voting results are often manipulated. In addition conventional selection is deemed inaccurate and time-consuming and costly. In this study the aim of this research is to design an information system e-voting that can be used for the Election of the Village Head of Cemandi, Sedati, Sidoarjo, East Java, where by using this system the election process becomes easier by ensuring the accuracy of the vote count. This system development method uses the model of software engineering waterfall. The test results blackbox show that the functions of the features in the system are running well. Based on the UAT test, the system received an average percentage rate of 86%.